A systematic approach to learning needs analysis - Latynin, M. A.; Melnykov, A. F.; Kobzev, I. V.; Kosenko, A. V.; Kosеnko, V. V. (BoScience Publisher, 2022)
The article defines the features of professional training of civil servants in the context of the formation of a new paradigm of state management of labor resources, which provides for ensuring its dependence on factors of the external socioeconomic environment, the orientation of civil servants towards the development of public-private partnerships, the relationship of training with active self-education
Keywords: systems of training; retraining and advanced training of civil servants; educational needs; civil service; professional training